Per-oral pancreatoscopy-guided lithotripsy vs. extracorporeal shock wave lithotripsy for treating refractory main pancreatic duct stones in chronic pancreatitis: Protocol for an open-label multi-center randomized clinical trial - Han, Samuel; Miley, Angelina; Akshintala, Venkata; Freeman, Martin L.; Kahaleh, Michel; Othman, Mohamed; Patel, Sandeep; Papachristou, Georgios I.; Raijman, Isaac; Sankey, Noel; Sayana, Hari; Singh, Vikesh; et al. (Pancreatology : official journal of the International Association of Pancreatology (IAP) ... [et al.], 2022)
Patients with chronic pancreatitis may develop pancreatic duct stones that can obstruct outflow leading to ductal hypertension and pain. Both endoscopic retrograde pancreatography (ERP) with per-oral pancreatoscopy (POP) and intraductal lithotripsy and extracorporeal shock wave lithotripsy (ESWL) are feasible options to attempt ductal stone clearance. This study aims to compare POP-guided lithotripsy with ESWL in the management of refractory symptomatic main pancreatic duct stones. This is an open-label, multi-center, parallel, randomized clinical trial. Patients with chronic pancreatitis and main pancreatic duct stones ≥5 mm who fail standard ERP methods for stone removal will be eligible for this study. In total, 150 subjects will be randomized 1:1 to either ESWL or POP. A maximum of 4 sessions of either ESWL or POP will be allowed in each arm, with crossover permitted thereafter. The primary outcome is complete stone clearance and secondary outcomes include quality of life, pain scores, number of interventions, and daily opiate requirements. This study aims to answer the question of which lithotripsy method is superior in removing refractory pancreatic duct stones while addressing the effects of lithotripsy on quality of life and pain in patients with chronic calcific pancreatitis (ClinicalTrials.gov NCT04115826).